Graphene-based optical switching system - Liu, Yingxiang (Nanyang Technological University, 2020)
The optical switch is a device used to turn on or off the optical circuit. It consists of mechanical, optical or electronic. In the network, we usually need to protect the switch to complete or interrupt the optical path. But traditional optical switches cannot identify the type of molecules. Due to this weakness, graphene as new material is designed in this project. Graphene consists of mono-atomic carbon atom sheets. Its inefficient light interaction influences the direct photon application. and it provides more effective magnetic susceptibility than the intrinsic material. When the light-matter interaction is enhanced by graphene plasma resonance, it can be used to identify molecular vibration modes. The small spectral linewidth is related to the probability of sudden change of scattering response. Thus, it can be used as an effective all-optical switch to moderate pumping intensity. Our final goal is to design a fast, cost-effective and energy-efficient active optical element based on graphene, which supports to future needs of society.